Dorel Fînaru, Lingvistica limbilor lumii. Institutul European, Iaşi, 2015; 418 pp. - Bleorţu, Cristina; García Rodríguez, Alba (El Colegio de México, 2017)
Se reseñó el libro: Lingvistica limbilor lumii.